2019
DOI: 10.4490/algae.2019.34.12.9
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of <italic>Ulva</italic> causing blooms from Jeju Island, Korea with new species, <italic>U. pseudo-ohnoi</italic> sp. nov. (Ulvales, Chlorophyta)

Abstract: Several species classified to the genus Ulva are primarily responsible for causing green tides all over the world. For almost two decades, green tides have been resulted in numerous ecological problems along the eastern coast of Jeju Island, Korea. In order to characterize the species of Ulva responsible for causing the massive blooms on Jeju Island, we conducted DNA barcoding of tufA and rbcL sequences on 183 specimens of Ulva from eight sites on Jeju Island. The concatenated analysis identified five bloom-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
2
11
0
3
Order By: Relevance
“…However, compared with these two molecular markers, the plastid elongation factor tufA was recommended by Saunders & Kucera (2010) as a more suitable barcode marker for most marine green macroalgae including the genus Ulva. This was further confirmed by Kirkendale et al (2013), Lee et al (2019) and Fort et al (2020b) for Australian, Korean and west European specimens, respectively, as they provided estimates of intra-and inter-specific divergence in Ulva species. Our current sequencing survey of hundreds of Ulva specimens along the French Atlantic coast found that many tufA sequences fully matched GenBank sequences of U. australis Areschoug and U. pertusa Kjellman, a junior synonym (see details in Couceiro et al, 2011), from Korea in the native area , and disjunct areas where the species has been introduced e.g.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, compared with these two molecular markers, the plastid elongation factor tufA was recommended by Saunders & Kucera (2010) as a more suitable barcode marker for most marine green macroalgae including the genus Ulva. This was further confirmed by Kirkendale et al (2013), Lee et al (2019) and Fort et al (2020b) for Australian, Korean and west European specimens, respectively, as they provided estimates of intra-and inter-specific divergence in Ulva species. Our current sequencing survey of hundreds of Ulva specimens along the French Atlantic coast found that many tufA sequences fully matched GenBank sequences of U. australis Areschoug and U. pertusa Kjellman, a junior synonym (see details in Couceiro et al, 2011), from Korea in the native area , and disjunct areas where the species has been introduced e.g.…”
Section: Introductionsupporting
confidence: 58%
“…All other tufA sequences (7 samples) with at least 2 mutations from tuH0 were from north-eastern Asia (Fig. 2) within the Yellow Sea from Donggang, China (Du et al, 2014) to Jeju Island, Korea (Kang et al, 2019;Lee et al, 2019). For simplicity, these tufA sequences were labelled tuH2 and tuH3, as they had 2 and 3 substitutions, respectively.…”
Section: Tufa Sequencesmentioning
confidence: 99%
“…2010, Lee et al. 2019), with overlaps between species morphologies, which raises questions about their genetic distinctness. Indeed, with such small phenotypical distinctions, one might expect their genetic diversity to be limited.…”
Section: Discussionmentioning
confidence: 99%
“…However, tufA and rbcL analyses indicate that U. fasciata and U. ohnoi could be resolved into separate lineages. If more species were included in the analysis, they could be even separated by U. spinulosa and U. reticulata [64,65]. Ulva fasciata and U. ohnoi shared only a few complementary/palindromic repeats and contained no forward or tandem repeats in their chloroplast genomes and mitogenomes.…”
Section: Plos Onementioning
confidence: 99%